2019
DOI: 10.1111/ger.12402
|View full text |Cite
|
Sign up to set email alerts
|

Loss of oral self‐care ability results in a higher risk of pneumonia in older inpatients: A prospective cohort study in a Japanese rural hospital

Abstract: Objectives To identify significant risk factors associated with incidence of mortality and pneumonia in whole‐community‐based older inpatients resident in Japanese rural region. Methods Patients older than 65 years admitted between 1 April and 15 April 2010 to a core hospital located in a rural region were exhaustively recruited, and incidence of mortality and pneumonia during the 32‐month follow‐up period were evaluated. Independent variables at baseline measurement included age, gender, body mass index, Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 34 publications
(47 reference statements)
0
14
0
Order By: Relevance
“…Malnutrition leads to the development of pneumonia and weakens the physical activity and immune system [5]. Therefore, adequate nutrition directly aids respiratory muscle function and immune defense mechanisms and provides high immunity against environmental pathogens in the lungs to reduce potential disease progression [6,7]. Therefore, the major role of nutrition in alleviating pneumonia is reducing malnutrition that induces high mortality and morbidity [8,9] and maintaining impaired respiratory muscle contractility [10].…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition leads to the development of pneumonia and weakens the physical activity and immune system [5]. Therefore, adequate nutrition directly aids respiratory muscle function and immune defense mechanisms and provides high immunity against environmental pathogens in the lungs to reduce potential disease progression [6,7]. Therefore, the major role of nutrition in alleviating pneumonia is reducing malnutrition that induces high mortality and morbidity [8,9] and maintaining impaired respiratory muscle contractility [10].…”
Section: Introductionmentioning
confidence: 99%
“…Adequate nutrition can enhance respiratory muscle function and immune defense ( 28 , 29 ). Therefore, nutritional intervention can control disease progression and improve respiratory function, thus reducing morbidity and mortality ( 30 ), hospitalization costs, and re-hospitalizations ( 31 , 32 ). Albumin level below 3.5 mg/dL suggests a poor nutritional status and survival ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…A key determinant of child malnutrition is socioeconomic vulnerability. Southeast Asia and Africa report that the incidence of malnutrition among girls has risen regularly in contrast to boys (Fujiwara et al, 2019). For example, Bangladesh research has shown a higher rate of malnutrition (54 percent) among females and a higher risk (1,44 times) of malnutrition compared to males (Zysman et al, 2019).…”
Section: Discussionmentioning
confidence: 99%